FORMULASI KEBIJAKAN PEMERINTAH TIMOR-LESTE DALAM PERLINDUNGAN HAK ANAK BERMASALAH DENGAN HUKUM (STUDI DI KEMENTRIAN KEHAKIMAN) - Cipriano da Costa Gino das Neves Gino das Neves; Sumartono .; Andy Fefta Wijaya (REFORMASI, 2015)
Policy Formulation the Government of Timor-Leste in the protection of the rights of children in conflict with the law, as efforts to implement the Convention on the Rights of the Child was ratified in 2003. The purpose of this study is to describe and analyze the formulation of government policy of Timor-Leste in the protection of the rights of children in trouble with the laws and the types of methods used in this research is descriptive with qualitative approach and interactive models as data analysis techniques. The study's findings indicate that the formulation of government policy Timor-Leste based strategic plan Government of Timor-Leste in the justice sector; human resources owned by the Ministry of Justice, particularly in the National Legislative Agency is very minimal and also public participation in policy formulation; cooperation built by the National Legislation Agency nice fellow public agencies and private organizations for this to be effective at all; National Legislation Agency is government agencies that fund is not an issue; In carrying out its duties and functions very not optimal because it has so far not been successful National Legislation Agency pouring a policy on the protection of children's rights into the format of a particular regulation.